2016
DOI: 10.4049/jimmunol.1501591
|View full text |Cite
|
Sign up to set email alerts
|

TIGIT Enhances Antigen-Specific Th2 Recall Responses and Allergic Disease

Abstract: T cell Ig and ITIM domain receptor (TIGIT), expressed on T, NK, and regulatory T cells, is known as an inhibitory molecule that limits autoimmunity, antiviral and antitumor immunity. In this report, we demonstrate that TIGIT enhances Th2 immunity. TIGIT expression was upregulated in activated Th2 cells from mice with experimental allergic disease and in Th2 polarization cultures. In addition, its high-affinity ligand CD155 was upregulated in mediastinal lymph node dendritic cells from allergic mice. In an in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 46 publications
5
38
1
Order By: Relevance
“…Furthermore, DW2008S and its two major constituents significantly reduced TIGIT expression in both concanavalin A‐activated spleen cells and polarized Th2 cells isolated from CD4 + T cells. Consistent with the results of a previous study, which showed increased TIGIT expression in the MLNs of mice with Th2‐driven allergic asthma,16 we observed that TIGIT expression was elevated in the MLNs of mice with allergic asthma. However, TIGIT expression was restored to its normal level by DW2008S.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Furthermore, DW2008S and its two major constituents significantly reduced TIGIT expression in both concanavalin A‐activated spleen cells and polarized Th2 cells isolated from CD4 + T cells. Consistent with the results of a previous study, which showed increased TIGIT expression in the MLNs of mice with Th2‐driven allergic asthma,16 we observed that TIGIT expression was elevated in the MLNs of mice with allergic asthma. However, TIGIT expression was restored to its normal level by DW2008S.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, TIGIT stimulates Th2 cell differentiation through its interaction with CD155 to promote the development of allergic disease 16. Therefore, we investigated whether TIGIT is involved in selective regulation of Th2 responses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations